Work and labour in the Bangladesh brackish-water shrimp export sector - Pokrant, Bob; Reeves, P. (2003)
This paper argues that discussions about the applicability of labour and environmental policies, standards and codes of conduct in Bangladesh must be based upon an understanding of the diverse local environmental, economic and social conditions under which people work and sustain their livelihoods. In the case of the shrimp export sector, such understanding is limited as no comprehensive study of the sector as whole and the role of labour and environmental issues within it has been carried out. The paper goes some way to filling this gap in our knowledge by drawing on the authors' continuing research on the shrimp export industry in Southeast Bangladesh and other sources to describe the different forms of work and labour in the industry's various sub-sectors, paying particular attention to processing plants, shrimp farms, wild fry collection and hatcheries. It shows the great diversity in work and environmental conditions in the sector, illustrates the relationship between work, labour and environment in the fry collecting sub-sector and makes recommendations for further research.